Studies on novel chiral sulfones - Lewis, Frank (Trinity College (Dublin, Ireland). School of Chemistry, 2008)
The research carried out in the present study focuses mainly on the synthesis of some novel chiral sulfones and the studies of their potential applications as chiral auxiliaries in asymmetric synthesis. This thesis is divided into four chapters: Chapter 1 summarises the different approaches to asymmetric synthesis with a particular focus on the chiral auxiliary approach . The most important chiral auxiliaries, including those derived from the chiral pool element camphor, are introduced and their modes of action and some illustrative applications in asymmetric synthesis are discussed. In addition , the chemistry of the sulfonyl functional group is summarised .
Keywords: Chemistry, Ph.D.; Ph.D. Trinity College Dublin